Molecular Docking and Dynamics Simulation Studies Uncover the Host-pathogen Proteinprotein Interactions in Penaeus Vannamei and Vibrio Parahaemolyticus - Nur Fathiah Rosilan; Muhamad Arif Mohamad Jamali; Siti Aishah Sufira; Khor Waiho; Hanafiah Fazhan; Noraznawati Ismail; Yeong Yik Sung; Zeti-Azura MohamedHussein; Azzmer Azzar Abdul Hamid; Nor Afiqah-Aleng (Plos One, 2024)
Indexed by Scopus/ERA